Energy Policies and Investments Around Solar & Wind Energy in India: A Review - Gaurav Kumar; Shaifali; Anoop Kumar (International Journal of Sustainability, 2024)
India is a fast-moving economy and in this race of making our country a world power India is moving aggressively towards attaining its commitment to renewable energy goals. Our country India set an ambitious target of achieving 175 GW of renewable energy volume by 2022 and aim to achieve 500 GW by 2030. Bharat has in mind to move toward the Two Degree Celsius climate change objective under Nationally Determined Contributions in 2015 which has put one’s mark on 15% of renewable amalgamation in the foremost energy mix by 2020. Solar and wind energy are the more focused energies on which we are dependent more than any other form of the renewable energy. India like many other developing countries committed towards the net-zero emission and for that government of India form the energy policies for the better implementation of the renewable energy on the grass root level. Bharat’s Renewable Energy Programme is unparalleled and the most widespread among the developing nations of the World. The supreme authorities have designed some policies, programs, and an unconventional environment to attract foreign investments to move forward the nation into the renewable market at an increasing pace. This study reflects eloquent policies and investment openings in energy due to the development of renewable production in Bharat. The most important ans demanding issue facing Bharat’s subsidy framework is the lack of imaginative money involving options that will present larger amounts at less interest rates and for extended and long durations. Overall, sound financing and good policies will give pace to the process of production of energy, ultimately transforming to accelerated renewable growth.
Keywords: Renewable energy; Solar Energy; Wind Energy; future potentials; investments; policies in India